2007
DOI: 10.1192/bjp.bp.107.036764
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effectiveness of treatments for anorexia nervosa in adolescents

Abstract: First-line in-patient psychiatric treatment does not provide advantages over out-patient management. Out-patient treatment failures do very poorly on transfer to in-patient facilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
172
2
16

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(193 citation statements)
references
References 35 publications
(47 reference statements)
3
172
2
16
Order By: Relevance
“…In contrast, the large population-based RCT in adolescents with AN [13] found only low full recovery rates.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…In contrast, the large population-based RCT in adolescents with AN [13] found only low full recovery rates.…”
Section: Introductionmentioning
confidence: 80%
“…Furthermore, 77.2% of the patients participating in this study suffered from psychiatric comorbidities at the beginning of the treatment and had a very low BMI. Gowers et al [13] assessed the clinical effectiveness of adolescent inpatient treatment and found likewise a rather poor outcome. Our findings amplify the assumption that for many patients, AN is a troublesome part of their life for many years [4,15,25,27].…”
Section: Discussionmentioning
confidence: 99%
“…A AN, por causa de suas graves consequências nos sistemas orgânicos decorrentes da desnutrição, é o diagnóstico de TA mais prevalente nas intervenções hospitalares [22][23][24] . A distribuição dos pacientes internados pelo GRATA de acordo com o diagnóstico também demonstrou preponderância de AN, sobretudo em seu subtipo restritivo.…”
Section: Discussionunclassified
“…No presente estudo, a média de idade mais baixa foi encontrada entre pacientes com AN (21,7 anos). Entretanto, esse valor é superior às médias demonstradas em outros estudos, que variaram de 10 a 20,7 anos 11,21,22,23,25,26 .…”
Section: Discussionunclassified
“…A Anorexia nervosa, devido às suas graves consequências nos sistemas orgânicos decorrentes da desnutrição 22,23 , associada à gravidade ainda maior quando diagnosticada em crianças e adolescentes por influenciar diretamente o desenvolvimento e o crescimento 24,25 , torna-se o diagnós- tico de TA mais prevalente nas intervenções hospitalares [26][27][28] . A distribuição dos pacientes internados pelo GRATA de acordo com o diagnóstico, demonstrou preponderância de AN, sobretudo em seu subtipo restritivo.…”
Section: S C U S S ã Ounclassified